Analisis Proses Recruitment Sumber Daya Manusia Crew kapal Pada Perusahaan Jasa Pelayaran ( Studi Kasus Pada Manning Agent PT. KSM Indonesia) - Ikhsan, Nur El; Chaniago, Rifaldy Aditya Pratama (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The purpose of this research is to analyze how the recruitment process of providing Human Resources for Ship Crew in PT KSM Indonesia. In addition, to analyze the management of Human Resources at PT KSM Indonesia in improving the quality of the crew at the company. This research method uses descriptive qualitative methods. The data collection techniques used in this research are observation and interview techniques. The results of this study indicate that the recruitment process carried out by PT KSM Indonesia is in accordance with the SOP originating from Korea, one of which is the Marine Test and there are additional procedures based on needs so that in this recruitment process it has been carried out in accordance with the applicable SOP. The results also show that the management of Human Resources at PT KSM Indonesia still has to be improved again by prioritizing a more structured level of quality of human resources, because the company must prioritize the quality of the crew to achieve a company's vision and mission. So far the process carried out by PT KSM Indonesia in the process of recruiting and managing Human Resources is quite good because it is based on its default SOP which originated from Korea, it's just that PT KSM Indonesia must have its own SOP in order to increase the effectiveness and efficiency of the company.